Strengthening health systems for health emergency preparedness and response in Africa: integrating building system resilience to achieve universal health coverage and promote health security is a “double win” - Talisuna, Ambrose Otau; Karamagi, Humphrey Cyprian; Saikat, Sohel; Droti, Benson; Bisoborwa, Geoffrey K.; Nabyonga-Orem, Juliet; Chamla, Dick; Gueye, Abdou Salam; Kasolo, Francis Chisaka (Frontiers in Tropical Diseases, 2025)
Africa continues to face numerous public health and humanitarian crises, including infectious disease epidemics and pandemics. These shocks have major impacts on health systems and socio-economic development. While countries have made progress in implementing the International Health Regulations (2005), the COVID-19 pandemic and the 2014-2016, West Africa Ebola Virus Disease epidemic revealed major inadequacies in containing major public health emergencies effectively and promptly. In an instant, these shocks brought the world to a standstill– tragically costing many lives with a severe toll on communities, societies, and economies. In this perspective, we urge African countries to accelerate integrating health security reforms into broader health systems strengthening. We propose a logical, system-wide approach, including a comprehensive gap assessment and analysis, followed by holistic planning and comprehensive reforms for improving key dimensions, including, service delivery, organizational and management processes; governance, leadership and coordination; predictable, scalable, and sustainable financing; surveillance and health information systems; quantity, quality and distribution of the health and care workforce; resilient health infrastructure; and finally local/regional manufacturing and procurement and supply chain management systems for health products and technologies. Positioning health security reforms as part of overall health systems strengthening will advance the primary health care approach, promote health security, and accelerate the achievement of universal health coverage (UHC). The latter will lead to equitable access to essential health services; better provision of efficient emergency response; and ultimately improved population health. Integrating investment in health security and UHC is a “double-win” and a pathway to achieve resilience.